A catalyst composition for polyester, a hydrolysis-resistant polyester film, and a method for its preparation.

By using a composition of aluminum compound and borate in the polyester catalyst, the content of the mid-terminal carboxyl group and diethylene glycol of the polyester is reduced, and the problems of complex and high cost of catalyst preparation in the prior art are solved, thereby achieving high hydrolysis resistance and low production costs of the polyester.

CN115873224BActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202111149256.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-29
Publication Date
2025-03-07
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

The preparation process of existing polyester catalysts is complex and costly, and it is necessary to improve the hydrolysis resistance of the polyester by adding additives, resulting in increased production costs and reduced performance.

Method used

An intermediate solution is prepared by reacting aluminum compounds, acidic substances and diols. Borate salt is added to form an aluminum compound solution, which is used to catalyze the esterification and polycondensation reaction of polyester and reduce the content of the middle-end carboxyl group and diethylene glycol of the polyester.

Benefits of technology

The content of carboxyl and diethylene glycol in the middle-end polyester is reduced, which significantly improves the hydrolysis resistance of polyester, simplifies the preparation process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003286604660000141
    Figure BDA0003286604660000141
Patent Text Reader

Abstract

The present invention discloses a catalyst composition for polyester, a hydrolysis-resistant polyester film and a preparation method. The catalyst composition is prepared from raw materials including an aluminum compound, an acidic substance, a diol and a borate. In the method for preparing the hydrolysis-resistant polyester film of the present invention, the in-situ introduction of the aluminum compound solution effectively reduces the terminal carboxyl content in the polyester, and the hydrolysis resistance of the polyester is significantly improved. The present invention does not need to add other auxiliary agents such as an anti-hydrolysis agent, a chain extender, and a heat stabilizer, and has the advantages of not reducing the performance of the catalyst, having a significant effect, good versatility and operability, and high production efficiency, and is particularly suitable for the continuous production of hydrolysis-resistant polyester films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyester materials, and in particular relates to a catalyst composition for polyester, a hydrolysis-resistant polyester film and a preparation method thereof. Background Art

[0002] Polyester is a general term for a class of high molecular polymers generated by esterification and polycondensation of polyols and polyacids. In general, polyester mainly refers to polyethylene terephthalate, which is obtained by polycondensation of purified terephthalic acid and ethylene glycol. Because PET has many excellent physical, chemical and mechanical properties, it is widely used in containers, packaging materials, films, bottles, films, plastics and other fields. However, polyester chips produced by conventional polyester catalysts such as antimony polyester catalysts and titanium polyester catalysts contain more residual terminal carboxyl and hydroxyl groups in the polyester chain, so under high temperature and high humidity, polyester will undergo a side reaction of segment hydrolysis. Therefore, with the increase of the terminal carboxyl content in the polyester chips, its hydrolysis resistance gradually decreases, causing the mechanical and mechanical properties of polyester downstream products to seriously decrease, or the aging speed to accelerate under the use environment, so that the polyester products cannot reach the expected service life. This limits the use of polyester products in certain fields, especially the fluorine-free solar PET backplane industry.

[0003] In recent years, with the strong support of the country for the photovoltaic industry, the photovoltaic solar cell industry has developed rapidly. During the use of photovoltaic cells, photovoltaic modules must withstand environmental influences, which may change greatly depending on the surrounding climate. Among them, the photovoltaic backplane is on the back of the photovoltaic cell, protecting and supporting the cell. It is a photovoltaic encapsulation material that is directly in contact with the surrounding environment over a large area. It should have excellent aging resistance (humid heat, dry heat, ultraviolet), electrical insulation, water vapor barrier and other properties. According to the chemical composition, photovoltaic backplanes are mainly divided into two categories: fluorine-containing backplanes and fluorine-free backplanes. Although fluorine-containing backplanes have good weather resistance, they are expensive, require high recycling technology, and are prone to environmental pollution. Some PET materials with strong hydrolysis resistance have gradually been used in photovoltaic backplanes. Compared with conventional polyester films, PET films for backplanes should have better aging resistance, electrical insulation resistance and dimensional stability. The end carboxyl content of the polyester chips used for film formation is required to be lower than that of conventional polyester chips. In addition, when the content of diethylene glycol in polyester chips is high, the ether bonds in the polyester chain segments are easily degraded and broken when exposed to water. Therefore, the diethylene glycol content of polyester chips used in the production of bare back solar backsheets must also be kept at a low range. Only then will PET have good hydrolysis resistance and aging resistance. Further improving the hydrolysis resistance and aging resistance of fluorine-free backsheets is a key technical difficulty that needs to be solved in the production of polyester chips for photovoltaic backsheet films.

[0004] Ordinary polyesters are difficult to meet the requirements of photovoltaic backplane films in terms of hydrolysis resistance, aging resistance, etc. Existing relevant documents CN110183629A, CN102575027A, CN103627150A, CN105542138A, etc. adopt new manufacturing methods to manufacture hydrolysis-resistant and aging-resistant polyesters to meet the requirements of photovoltaic backplane films.

[0005] Patent CN 110183629A discloses a method for preparing a composition for hydrolysis-resistant polyester and a composition solution. In the patent, an aluminum-titanium composite catalyst is used to prepare PET slices, and the terminal carboxyl content in the prepared polyester slices is reduced, and the hydrolysis resistance is good. The disadvantages of this method are: (1) the catalyst needs to contain aluminum compounds and titanium compounds, the preparation method is complicated, the production cost is high, and the introduction of titanium compounds makes the slices have a poor hue; (2) the phosphorus compounds introduced into the catalyst system, such as trimethyl phosphate and triethyl phosphate, inhibit the catalytic activity of the aluminum compounds, so it is necessary to increase the amount of aluminum compounds added, which causes an increase in the amount of foreign matter, and there is a tendency for frequent filter replacement in the melt extrusion process during film manufacturing, and an increase in film defects.

[0006] Patent CN 102575027A discloses a method for preparing a polyester film for a back protective film of a solar cell. In this method, a phosphorus compound having an aromatic group in the molecule is introduced during the synthesis of the catalyst. Although such a phosphorus compound having an aromatic group can improve the catalytic activity of an aluminum compound, its preparation process is complicated and expensive, resulting in a sharp increase in the cost of PET slices, which is not conducive to the industrial production of PET-based photovoltaic backplanes.

[0007] Patent CN 103627150A discloses a method for preparing a polyester material and a polyester film, in which a reactive phosphorus-based flame retardant is added during the synthesis of the polyester material, and a chain extender and an anti-hydrolysis agent polycarbodiimide are added in the later stage of polycondensation. The method adds flame retardants, chain extenders, and anti-hydrolysis agents, which greatly increases the production cost. The addition of flame retardants makes the slices yellow; the role of adding anti-hydrolysis agent polycarbodiimide is to reduce the occurrence of degradation reactions during the processing of polyester into films, but it cannot prevent the generation of more terminal carboxyl groups during the preparation of PET. In addition, the presence of polycarbodiimide is harmful to the environment and the human body, and will reduce the optical and mechanical properties of the material to a certain extent.

[0008] Patent CN 105542138A discloses a method for preparing polyester slices for solar cell backplane films. In the method, nano- or micro-sized titanium dioxide, calcium carbonate, and barium sulfate are added during the synthesis of polyester. The reaction is completed in two steps: liquid phase and solid phase polycondensation. Due to the addition of the solid phase polycondensation step, the production cost is significantly increased. The final terminal carboxyl content depends on the process control of the solid phase polycondensation. At the same time, the effect of the diethylene glycol content on the hydrolysis resistance during the slice synthesis process is not considered.

[0009] It can be seen that although the existing methods can improve the hydrolysis resistance of polyester to varying degrees, they have disadvantages such as high catalyst cost, lack of versatility, easy film defects, and poor operability. At the same time, the existing technology usually adds other additives such as hydrolysis resistance agents, chain extenders, heat stabilizers, nucleating agents, etc. in the preparation process of polyester film to improve the hydrolysis resistance of polyester and further improve the hydrolysis resistance of polyester film, rather than the polyester structure itself having low terminal carboxyl groups and low diethylene glycol content. Therefore, it is urgent to develop new methods to improve the hydrolysis resistance of polyester to meet the requirements of photovoltaic PET backsheet for hydrolysis resistance. Summary of the invention

[0010] In order to solve the problems that, in the process of preparing hydrolysis-resistant polyester chips, the catalyst preparation process is complicated, the synthesis cost is high, and the hydrolysis resistance of polyester needs to be improved by adding auxiliary agents, the present invention discloses a catalyst composition for polyester, a hydrolysis-resistant polyester film and a preparation method thereof. The polyester prepared by the catalyst of the present invention does not need end-capping and / or chain extension treatment, the obtained polyester has low terminal carboxyl and diethylene glycol contents, the prepared polyester film has good water resistance, and the preparation process is simple and the cost is low.

[0011] One of the purposes of the present invention is to provide a catalyst composition for polyester, which is prepared from raw materials including aluminum compounds, acidic substances, diols and borates.

[0012] In a preferred embodiment, the aluminum compound is selected from at least one of aliphatic carboxylates of aluminum, halogenated carboxylates of aluminum, hydroxycarbonates of aluminum, inorganic acid salts of aluminum, organic sulfonates of aluminum, organic sulfates of aluminum, alkoxides of aluminum, acetylacetonates of aluminum, aluminum oxides, and hydroxides of aluminum; including but not limited to aliphatic carboxylates selected from formates, acetates, propionates, butyrates, oxalates, acrylates, methacrylates, etc.; halogenated carboxylates selected from trichloroacetates, trifluoroacetates; selected from lactates, citric acid salts, etc. The invention relates to a hydroxycarbonate selected from a salt of oxalate or oxalate; an inorganic acid salt selected from carbonates, sulfates, nitrates, phosphates, phosphonates, phosphinates, bisulfates, bicarbonates, hydrogen phosphates, sulfites, thiosulfates, hydrochlorides, hydrobromides, chlorides, chlorates, bromides and bromates; an organic sulfonate selected from 1-propanesulfonate, 1-pentanesulfonate and naphthalenesulfonate; an organic sulfate selected from dodecyl sulfate; an alcohol salt selected from methoxide, ethoxide, propoxide and butoxide; at least one of acetylacetonate and oxide.

[0013] In a more preferred embodiment, the aluminum compound is selected from at least one of aluminum formate, aluminum acetate, aluminum propionate, aluminum butyrate, aluminum oxalate, aluminum acrylate, aluminum methacrylate, aluminum trichloroacetate, aluminum trifluoroacetate, aluminum lactate, aluminum citrate, aluminum oxalate, aluminum carbonate, aluminum sulfate, aluminum nitrate, aluminum phosphate, aluminum phosphonate, aluminum phosphite, sodium aluminate, aluminum hydrogen sulfate, aluminum hydrogen carbonate, aluminum hydrogen phosphate, aluminum sulfite, aluminum thiosulfate, aluminum hydrochloride, aluminum chloride, polyaluminum chloride, aluminum chlorate, aluminum bromide, 1-propanesulfonate aluminum, 1-pentanesulfonate aluminum, aluminum naphthalenesulfonate, dodecyl aluminum sulfate, aluminum methoxide, aluminum ethoxide, aluminum propoxide, aluminum isopropoxide, aluminum butoxide, aluminum glycol, and aluminum acetylacetonate, and is further preferably selected from at least one of aluminum chloride, polyaluminum chloride, aluminum acetylacetonate, sodium aluminate, aluminum acetate, aluminum isopropoxide, or aluminum glycol.

[0014] In a preferred embodiment, the acidic substance is selected from at least one or more of aliphatic carboxylic acids, hydroxycarbonic acids, inorganic acids and organic sulfonic acids. Including but not limited to aliphatic carboxylic acids selected from formic acid, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid; hydroxycarbonates selected from lactic acid, citric acid, oxalic acid; inorganic acids selected from carbonic acid, sulfuric acid, nitric acid, phosphoric acid, chloric acid, bromic acid, boric acid; at least one organic sulfonic acid selected from 1-propanesulfonic acid, 1-pentanesulfonic acid, naphthalenesulfonic acid. Preferably, it is selected from at least one of lactic acid, citric acid, oxalic acid, acetic acid, or boric acid.

[0015] In a preferred embodiment, the borate is selected from at least one of lithium borate, lithium metaborate, lithium methyltriol borate, lithium tetramethoxyborate, lithium triphenyl-n-butylborate, potassium borate, potassium tetrafluoroborate, potassium tetraphenylborate, 2-phenylethyl potassium trifluoroborate, sodium tetraborate, sodium metaborate, sodium tetraphenylborate, sodium aminoborate, sodium tetrafluoroborate, sodium tetra(p-tolyl)borate, magnesium borate, ferrocene borate, ferric tetrafluoroborate, zinc borate or zinc tetrafluoroborate, preferably selected from at least one of lithium borate, potassium borate, sodium tetraborate and magnesium borate.

[0016] In a preferred embodiment, the diol is selected from aliphatic diols, preferably at least one selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol, more preferably ethylene glycol.

[0017] In a preferred embodiment, the molar ratio of the aluminum element in the aluminum compound to the diol is 1:(5-50), preferably 1:(10-30), and specifically can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, etc.

[0018] In a preferred embodiment, the molar ratio of the aluminum element in the aluminum compound to the acidic substance is 1:(1-10), preferably 1:(1-5), and specifically can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0019] In a preferred embodiment, the molar ratio of the aluminum element in the aluminum compound to the metal element in the borate is 1:(0.01-10), preferably 1:(0.5-5), and specifically can be 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0020] The second object of the present invention is to provide a method for preparing the catalyst composition, comprising reacting an aluminum compound, an acidic substance and a diol to obtain an intermediate solution, adding a borate to the intermediate solution, and reacting to obtain the catalyst composition.

[0021] In a preferred embodiment, the aluminum compound, the acidic substance and the diol are reacted at 60-120° C. for 0.5-4 h, preferably at 60-90° C. for 0.5-2 h.

[0022] In a preferred embodiment, the borate and the intermediate solution are reacted at 90-150° C. for 0.5-4 h, preferably at 90-110° C. for 0.5-2 h.

[0023] The third object of the present invention is to provide a method for preparing a hydrolysis-resistant polyester film, comprising the following steps:

[0024] (1) mixing a dibasic acid, a diol, and the above-mentioned catalyst composition, and performing an esterification reaction and a polycondensation reaction to prepare a hydrolysis-resistant polyester;

[0025] (2) The polyester prepared in step (1) is subjected to melt extrusion, sheet casting, biaxial stretching, heat setting, cooling and winding to obtain the hydrolysis-resistant polyester film.

[0026] In a preferred embodiment, the dibasic acid is selected from aromatic dicarboxylic acids and / or alicyclic carboxylic acids, more preferably at least one selected from terephthalic acid, phthalic acid, isophthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid and cyclohexane dicarboxylic acid, more preferably terephthalic acid.

[0027] In a preferred embodiment, the diol is selected from aliphatic diols, more preferably at least one selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.

[0028] In a preferred embodiment, in step (1), the dibasic acid and the diol are first subjected to an esterification reaction at 210-270° C. and a pressure of 0.1-0.3 MPa; after the esterification is completed, the reaction system is gradually decompressed and heated to 275-285° C. and a pressure of less than 100 Pa to carry out a polycondensation reaction; wherein the catalyst composition is added before the esterification reaction or between the esterification reaction and the polycondensation reaction, preferably before the esterification reaction.

[0029] In a preferred embodiment, based on the amount of polyester produced, the weight of aluminum atoms in the catalyst composition is 10 to 200 ppm, preferably, the weight of aluminum atoms is 20 to 100 ppm, specifically 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 150 ppm, 200 ppm, etc.

[0030] In a preferred embodiment, the hydrolysis-resistant polyester obtained in step (1) has a terminal carboxyl content of 1 to 20 mmol / kg, a diethylene glycol content of 0.1 to 10%, and an intrinsic viscosity of 0.6 to 1.0 dL / g. More preferably, the terminal carboxyl content is 1 to 12 mmol / kg, the diethylene glycol content is 0.1 to 2%, and the intrinsic viscosity is 0.6 to 0.9 dL / g.

[0031] In a preferred embodiment, in step (2), the extrusion temperature is 255-285°C; the temperature of the casting roller is lower than 60°C; the stretching temperature during longitudinal stretching is 80-110°C, and the stretching ratio is 2-5 times; the stretching temperature during transverse stretching is 110-140°C, and the stretching ratio is 2-5 times; the heat setting temperature is 190-240°C; and the cooling temperature is lower than 100°C.

[0032] A fourth object of the present invention is to provide a polyester film obtained by the preparation method.

[0033] A fifth object of the present invention is to provide application of the polyester film in photovoltaic backsheets.

[0034] The polyester film prepared by the present invention has excellent hydrolysis resistance and can meet the performance requirements of the polyester film in the photovoltaic back sheet.

[0035] The present invention adds an aluminum compound solution in situ into the catalytic reaction system, and the aluminum element can form a complex with the terminal carboxyl group of the polyester macromolecular chain to seal it, thereby reducing the terminal carboxyl content in the final product. The addition of borate can not only interact with the aluminum metal catalytic center to improve the polymerization activity of aluminum, thereby avoiding the introduction of phosphoric acid compounds, but also react with the terminal hydroxyl group of the polyester to form a boric acid ester during the high-temperature polymerization process of the polyester to seal the unstable terminal hydroxyl group, thereby improving the hydrolysis resistance of the polyester. The present invention is essentially different from the conventional method of improving the hydrolysis resistance of polyester, such as adding other auxiliary agents such as hydrolysis resistance agents, chain extenders, heat stabilizers, nucleating agents, etc., and has the advantages of not reducing the catalyst performance, significant effect, good versatility and operability, high production efficiency, etc., and is particularly suitable for the continuous production of highly hydrolysis-resistant polyester.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The preparation method of the aluminum compound solution is simple, the catalyst activity is high, and the overall cost is low;

[0038] (2) Introducing an aluminum compound solution into the catalyst system can significantly reduce the terminal carboxyl content and diethylene glycol content of the polyester product, and the hydrolysis resistance of the polyester product is significantly improved;

[0039] (3) In the preparation process of hydrolysis-resistant polyester film, no other additives such as hydrolysis-resistant agent, chain extender, heat stabilizer, nucleating agent, etc. are needed, which saves resources, has a simple preparation method and is easy for industrial production;

[0040] (4) The prepared low-end carboxyl and low-diglycol polyester is used to directly prepare polyester film. The prepared polyester film has excellent hydrolysis resistance and can meet the performance requirements of polyester film in photovoltaic modules, thus promoting the stable development of China's PET-based photovoltaic solar cell backplane. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0042] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0043] According to a preferred embodiment of the present invention, the method for preparing the hydrolysis-resistant polyester film may include the following steps:

[0044] Step (a): heating an aluminum compound, an acidic substance and a diol for a period of time to obtain an intermediate solution, adding a borate compound to the intermediate solution, and heating the reaction for a period of time to obtain an aluminum compound solution;

[0045] Step (b): mixing a dibasic acid, a diol and an aluminum compound solution, performing an esterification reaction to prepare a polyester ester, and then performing a polycondensation reaction under vacuum to prepare a low-terminal carboxyl group, low-diglycol hydrolysis-resistant polyester;

[0046] Step (c): extruding the low-end carboxyl and low-diglycol hydrolysis-resistant polyester prepared in step (b) through a melt pipe through a T-die, casting, biaxial stretching, heat setting, cooling and winding to obtain a hydrolysis-resistant polyester film with a thickness of 50 μm to 500 μm.

[0047] In a preferred embodiment, in the step (a), the aluminum compound, the acidic substance, and the diol are added, and stirred at 60-120°C for 0.5-4h. Preferably, the aluminum compound, the acidic substance and the diol are mixed at 60-90°C and stirred for 0.5-2h. After the borate is added, the mixture is stirred at 90-150°C for 0.5-4h. Preferably, the mixture is stirred at 90-110°C for 0.5-2h.

[0048] In a preferred embodiment, in the step (b), the dicarboxylic acid and the diol are first subjected to an esterification reaction at 210-270° C. and a pressure of 0.1-0.3 MPa; after the esterification is completed, the reaction system is gradually decompressed and heated to 275-285° C. and a pressure of less than 100 Pa to carry out a polymerization reaction; wherein the aluminum compound solution is added before the esterification reaction or between the esterification reaction and the polymerization reaction, preferably before the esterification reaction.

[0049] In a preferred embodiment, an aluminum compound solution is added in step (b), and the weight of aluminum atoms is 10 to 200 ppm based on the amount of polyester produced, preferably 20 to 100 ppm based on the amount of polyester produced.

[0050] In a preferred embodiment, the low terminal carboxyl and low diethylene glycol hydrolysis-resistant polyester prepared in step (b) has a terminal carboxyl content of 1 to 20 mmol / kg, a diethylene glycol content of 0.1 to 10%, and an intrinsic viscosity of 0.6 to 1.0 dL / g.

[0051] In a preferred embodiment, in the step (c), the melt tube extrusion temperature is 255-285°C, the temperature of the casting roller is lower than 60°C, the stretching temperature during longitudinal stretching is 80-110°C, and the stretching ratio is 2-5 times, the stretching temperature during transverse stretching is 110-140°C, and the stretching ratio is 2-5 times, the heat setting temperature is 190-240°C, the cooling temperature is lower than 100°C, and after cooling, the film is rolled up to obtain a hydrolysis-resistant polyester film.

[0052] In the present invention, the intrinsic viscosity, terminal carboxyl content, diethylene glycol content, elongation at break retention rate of the polyester film, etc. are analyzed and tested by the following methods:

[0053] (1) Intrinsic viscosity IV: Weigh about 0.125 g of sliced ​​sample and dissolve it in a mixed solvent of phenol / tetrachloroethane (mass ratio is 1:1) and measure it at 25±0.5℃ using an Ubbelohde viscometer.

[0054] (2) Terminal carboxyl content -COOH: Using the volumetric analysis method, take about 0.50 g of the slice sample and dissolve it in a mixed solution of phenol / chloroform (volume ratio of 2:3), and titrate it with a sodium hydroxide / methanol / benzyl alcohol standard solution.

[0055] (3) Diethylene glycol content DEG: Determined by hydrazine hydrolysis method using Shimadzu GC-TAG hydrogen flame gas chromatograph.

[0056] (4) Elongation retention of polyester film at break: According to ISO 527-3 standard, the test was conducted using Instron's 3344 material testing machine, and the processing software was Bluehill 2.31 version. The film was cut into Type 5 in the longitudinal direction (MD) of ISO 527-3 standard and placed in a Bluepard BPS-100CB constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) of Shanghai Yiheng Scientific Instrument Co., Ltd. for 24 hours. During the test, the initial clamp spacing was 75 mm, the test tensile rate was 100 mm / min, and each sample was tested at least 5 times, and the average value was taken.

[0057] [Example 1]

[0058] Preparation of aluminum compound solution:

[0059] Aluminum glycol (0.2 mol), lactic acid (0.2 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, stirred and reacted at 60°C for 1 hour to obtain an intermediate solution, lithium borate (0.2 mol) was added to the intermediate solution, and the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain aluminum compound solution A.

[0060] Preparation of hydrolysis-resistant polyester chips:

[0061] 600 g of terephthalic acid, 300 g of ethylene glycol and aluminum compound solution A (based on the amount of polyester produced, the weight of aluminum atoms is 50 ppm) are mixed into a slurry and added to a polymerization kettle for esterification reaction. The esterification temperature is 230-255°C and the reaction pressure is 0.25 MPa. The water generated by the reaction is discharged through a rectification device. After the esterification is completed, the pressure is reduced to normal pressure, the reaction system is gradually heated to 255-280°C, and the pressure is reduced by vacuum until the pressure of the reaction system is less than 100 Pa. When the system reaction reaches a certain time, the reaction is stopped, and then the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled and pelletized.

[0062] Preparation of hydrolysis-resistant polyester film:

[0063] The fully dried polyester chips are extruded through a melt tube through a T-die, the extrusion temperature of the melt tube is 280°C, the temperature of the casting roller is lower than 35°C, and the hydrolysis-resistant polyester film is obtained through casting, biaxial stretching, heat setting, cooling and winding. The stretching temperature during longitudinal stretching is 80°C, the stretching ratio is 4 times, the stretching temperature during transverse stretching is 110°C, the stretching ratio is 4 times, the heat setting temperature is 190°C, and the cooling temperature is lower than 100°C. The thickness of the prepared hydrolysis-resistant polyester film is 80 μm.

[0064] [Example 2]

[0065] Preparation of aluminum compound solution:

[0066] Aluminum chloride (0.2 mol), citric acid (0.6 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, stirred and reacted at 60°C for 1 hour to obtain an intermediate solution, potassium borate (0.6 mol) was added to the intermediate solution, and the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain an aluminum compound solution B.

[0067] Preparation of hydrolysis-resistant polyester chips:

[0068] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0069] Preparation of hydrolysis-resistant polyester film:

[0070] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0071] [Example 3]

[0072] Preparation of aluminum compound solution:

[0073] Aluminum lactate (0.2 mol), boric acid (1 mol) and ethylene glycol (10 mol) were placed in a 500 mL flask, and stirred at 60°C for 2 hours to obtain an intermediate solution. Sodium tetraborate (1 mol) was added to the intermediate solution, and the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain an aluminum compound solution C.

[0074] Preparation of hydrolysis-resistant polyester chips:

[0075] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0076] Preparation of hydrolysis-resistant polyester film:

[0077] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0078] [Example 4]

[0079] Aluminum acetate (0.2 mol), oxalic acid (0.5 mol) and ethylene glycol (5 mol) were placed in a 500 mL flask, and stirred at 60°C for 1 hour to obtain an intermediate solution. Magnesium borate (0.5 mol) was added to the intermediate solution, and the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain an aluminum compound solution D.

[0080] Preparation of hydrolysis-resistant polyester chips:

[0081] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0082] Preparation of hydrolysis-resistant polyester film:

[0083] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0084] [Comparative Example 1]

[0085] Preparation of aluminum compound solution:

[0086] Aluminum glycol (0.2 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, and stirred at 60°C for 1 hour to obtain an intermediate solution. Lithium borate (0.2 mol) was added to the intermediate solution, and the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain aluminum compound solution E.

[0087] Preparation of hydrolysis-resistant polyester chips:

[0088] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0089] Preparation of hydrolysis-resistant polyester film:

[0090] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0091] [Comparative Example 2]

[0092] Preparation of aluminum compound solution:

[0093] Aluminum glycol (0.2 mol), lactic acid (0.2 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, stirred and reacted at 60° C. for 1 hour to obtain an intermediate solution, then heated to 90° C. and stirred for 1.5 hours to obtain an aluminum compound solution F.

[0094] Preparation of hydrolysis-resistant polyester chips:

[0095] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0096] Preparation of hydrolysis-resistant polyester film:

[0097] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0098] [Comparative Example 3]

[0099] Preparation of aluminum compound solution:

[0100] Aluminum glycol (0.2 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, stirred and reacted at 60°C for 1 hour to obtain an intermediate solution, then the temperature was raised to 90°C and stirring was continued for 1.5 hours to obtain an aluminum compound solution G.

[0101] Preparation of hydrolysis-resistant polyester chips:

[0102] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0103] Preparation of hydrolysis-resistant polyester film:

[0104] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0105] [Comparative Example 4]

[0106] Preparation of aluminum compound solution:

[0107] Aluminum compound solution H is prepared by mixing aluminum glycol (0.2 mol), lactic acid (0.2 mol), ethylene glycol (4 mol) and lithium borate (0.2 mol) at room temperature.

[0108] Preparation of hydrolysis-resistant polyester chips:

[0109] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0110] Preparation of hydrolysis-resistant polyester film:

[0111] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0112] [Comparative Example 5]

[0113] Preparation of aluminum compound solution:

[0114] Aluminum glycol (0.2 mol) and ethylene glycol (4 mol) were placed in a 500 mL flask, and stirred at 60° C. for 1 hour to obtain an intermediate solution. Trimethyl phosphate (0.2 mol) was added to the intermediate solution, and the temperature was raised to 90° C. and stirring was continued for 1.5 hours to obtain an aluminum compound solution I.

[0115] Preparation of hydrolysis-resistant polyester chips:

[0116] The method is the same as that of Example 1 to obtain hydrolysis-resistant polyester chips.

[0117] Preparation of hydrolysis-resistant polyester film:

[0118] The method is the same as that of Example 1 to prepare a hydrolysis-resistant polyester film having a thickness of 80 μm.

[0119] Test Example 1

[0120] The polyester film samples prepared in Examples 1-4 and Comparative Examples 1-4 were steamed under high pressure for 48 hours at a temperature of 121±2° C., a relative humidity of 100%, and a pressure of 2 atm to test the longitudinal elongation at break retention of the films.

[0121] Table 1: Summary of product performance of examples and comparative examples

[0122]

[0123] It can be seen from Table 1 that:

[0124] (1) The terminal carboxyl group -COOH, diethylene glycol DEG content and hydrolysis resistance index in Examples 1 to 4 are significantly better than those in Comparative Examples 1 to 5, that is, the terminal carboxyl group and diethylene glycol content are lower and the hydrolysis resistance is good;

[0125] (2) Compared with Comparative Examples 1 and 2, the polymerization time of the end of the polyester chips with the same intrinsic viscosity obtained in Example 1 is short, and the results show that the introduction of acidic compounds and borates can improve the polycondensation activity of aluminum catalysts;

[0126] (3) Compared with Comparative Example 2, the terminal carboxyl and diethylene glycol contents of the polyester chips of Examples 1 to 4 are lower, and the elongation retention rate of the polyester film at break is higher. The results show that the introduction of borate can improve the hydrolysis resistance of polyester;

[0127] (4) Compared with Comparative Example 3, Examples 1 to 4 have high polymerization activity, low terminal carboxyl and diethylene glycol contents in the polyester chips, and high retention of elongation at break of the polyester film, indicating that the use of the aluminum compound solution alone cannot produce polyester chips with excellent hydrolysis resistance;

[0128] (5) Compared with Comparative Example 4, Examples 1 to 4 have high polymerization activity, low terminal carboxyl and diethylene glycol contents, and high retention of elongation at break of polyester films, indicating that simple mixing of aluminum elements, acidic substances, diols and borates cannot achieve the preparation of hydrolysis-resistant polyester chips and films.

[0129] (6) Compared with Comparative Example 5, Examples 1 to 4 have high polymerization activity, low terminal carboxyl and diethylene glycol contents, and high retention of elongation at break of polyester films, indicating that the catalyst obtained by the reaction of aluminum compounds and phosphorus compounds cannot be used to prepare hydrolysis-resistant polyester chips and films.

Claims

1. A catalyst composition for polyester, prepared from raw materials including an aluminum compound, an acidic substance, a diol, and a borate; the borate is selected from at least one of lithium borate, lithium metaborate, lithium methyltriol borate, lithium tetramethoxyborate, lithium triphenyl-n-butylborate, potassium borate, potassium tetrafluoroborate, potassium tetraphenylborate, 2-phenylethyl potassium trifluoroborate, sodium tetraborate, sodium metaborate, sodium tetraphenylborate, sodium aminoborate, sodium tetrafluoroborate, sodium tetra(p-tolyl)borate, magnesium borate, ferrocene borate, iron tetrafluoroborate, zinc borate, and zinc tetrafluoroborate.

2. The catalyst composition according to claim 1, characterized in that: The aluminum compound is selected from at least one of aluminum aliphatic carboxylates, aluminum halogenated carboxylates, aluminum hydroxycarbonates, aluminum inorganic acid salts, aluminum organic sulfonates, aluminum organic sulfates, aluminum alkoxides, aluminum acetylacetonates, aluminum oxides, and aluminum hydroxides.

3. The catalyst composition according to claim 2, characterized in that: The aluminum compound is selected from at least one of aluminum formate, aluminum acetate, aluminum propionate, aluminum butyrate, aluminum oxalate, aluminum acrylate, aluminum methacrylate, aluminum trichloroacetate, aluminum trifluoroacetate, aluminum lactate, aluminum citrate, aluminum oxalate, aluminum carbonate, aluminum sulfate, aluminum nitrate, aluminum phosphate, aluminum phosphonate, aluminum phosphite, sodium aluminate, aluminum hydrogen sulfate, aluminum hydrogen carbonate, aluminum hydrogen phosphate, aluminum sulfite, aluminum thiosulfate, aluminum hydrochloride, aluminum chloride, polyaluminum chloride, aluminum chlorate, aluminum bromide, 1-propanesulfonate aluminum, 1-pentanesulfonate aluminum, naphthalenesulfonate, dodecyl aluminum sulfate, aluminum methoxide, aluminum ethoxide, aluminum propoxide, aluminum isopropoxide, aluminum butoxide, aluminum glycol, and aluminum acetylacetonate.

4. The catalyst composition according to claim 1, characterized in that: The acidic substance is selected from at least one of aliphatic carboxylic acid, hydroxycarbonic acid, inorganic acid and organic sulfonic acid.

5. The catalyst composition according to claim 4, characterized in that: The acidic substance is selected from at least one of formic acid, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, lactic acid, citric acid, oxalic acid, carbonic acid, sulfuric acid, nitric acid, phosphoric acid, chloric acid, bromic acid, boric acid, 1-propanesulfonic acid, 1-pentanesulfonic acid, and naphthalenesulfonic acid.

6. The catalyst composition according to claim 1, characterized in that: The diol is selected from aliphatic diols.

7. The catalyst composition according to claim 6, characterized in that: The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol.

8. The catalyst composition according to claim 1, characterized in that: The molar ratio of the aluminum element in the aluminum compound to the diol is 1:(5-50); and / or, The molar ratio of the aluminum element in the aluminum compound to the acidic substance is 1:(1-10); and / or, The molar ratio of the aluminum element in the aluminum compound to the metal element in the borate is 1:(0.01-10).

9. The catalyst composition according to claim 8, characterized in that: The molar ratio of the aluminum element in the aluminum compound to the diol is 1:(10-30); and / or, The molar ratio of the aluminum element in the aluminum compound to the acidic substance is 1:(1-5); and / or, The molar ratio of the aluminum element in the aluminum compound to the metal element in the borate is 1:(0.5-5).

10. A method for preparing the catalyst composition according to any one of claims 1 to 9, comprising reacting an aluminum compound, an acidic substance and a diol to obtain an intermediate solution, adding a borate to the intermediate solution, and reacting to obtain the catalyst composition.

11. The method for preparing the catalyst composition according to claim 10, characterized in that: The aluminum compound, the acidic substance and the diol are reacted at 60 to 120° C. for 0.5 to 4 hours; The borate and the intermediate solution are reacted at 90-150° C. for 0.5-4 hours.

12. The method for preparing the catalyst composition according to claim 11, characterized in that: The aluminum compound, the acidic substance and the diol are reacted at 60 to 90° C. for 0.5 to 2 hours; The borate and the intermediate solution are reacted at 90-110° C. for 0.5-2 hours.

13. A method for preparing a hydrolysis-resistant polyester film, comprising the following steps: (1) mixing a dibasic acid, a diol, and a catalyst composition as claimed in any one of claims 1 to 9, and subjecting the mixture to esterification and polycondensation to prepare a hydrolysis-resistant polyester; (2) The polyester prepared in step (1) is subjected to melt extrusion, sheet casting, biaxial stretching, heat setting, cooling and winding to obtain the hydrolysis-resistant polyester film.

14. The method for preparing a polyester film according to claim 13, characterized in that: The dibasic acid is selected from aromatic dicarboxylic acids and / or alicyclic carboxylic acids; and / or, The diol is selected from aliphatic diols.

15. The method for preparing a polyester film according to claim 14, characterized in that: The dibasic acid is selected from at least one of terephthalic acid, phthalic acid, isophthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid and cyclohexane dicarboxylic acid; and / or, The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.

16. The method for preparing a polyester film according to claim 13, characterized in that In step (1): The dibasic acid and diol are first subjected to an esterification reaction at 210-270° C. and a pressure of 0.1-0.3 MPa. After the esterification is completed, the reaction system is gradually decompressed and heated to 275-285° C. and a pressure of less than 100 Pa to carry out a polycondensation reaction. The catalyst composition is added before the esterification reaction or between the esterification reaction and the polycondensation reaction.

17. The method for preparing a polyester film according to claim 16, characterized in that: The catalyst composition is added before the esterification reaction.

18. The method for preparing a polyester film according to claim 13, characterized in that: The catalyst composition may have an aluminum atom content of 10 to 200 ppm by weight based on the amount of polyester produced.

19. The method for preparing a polyester film according to claim 18, characterized in that: The weight of aluminum atoms is 20 to 100 ppm.

20. The method for preparing a polyester film according to claim 13, characterized in that In step (2): The extrusion temperature is 255-285°C; the temperature of the casting roller is lower than 60°C; the stretching temperature during longitudinal stretching is 80-110°C, and the stretching multiple is 2-5 times; the stretching temperature during transverse stretching is 110-140°C, and the stretching multiple is 2-5 times; the heat setting temperature is 190-240°C; and the cooling temperature is lower than 100°C.

21. The method for preparing a polyester film according to claim 13, characterized in that: The hydrolysis-resistant polyester obtained in step (1) has a terminal carboxyl content of 1 to 20 mmol / kg, a diethylene glycol content of 0.1 to 10%, and an intrinsic viscosity of 0.6 to 1.0 dL / g.

22. The polyester film obtained according to the preparation method according to any one of claims 13 to 21.

23. Use of the polyester film according to claim 22 in a photovoltaic back sheet.

Citation Information

Patent Citations

  • Polyester film for protection of back surfaces of solar cells

    CN102575027A

  • Preparation method of polyether material, polyether film and preparation method thereof

    CN103627150A

  • Preparation method of polyester chip for solar battery back film

    CN105542138A

  • Hydrolysis-resistant polyester composition and preparation method of the composition solution and application thereof

    CN110183629A

  • Method for preparing polyester and polyester manufactured by the method as well as polyester formed body

    CN101208371A